Study on association of serum lipoprotein(a) with coronary artery disease - Mohanraj, P.; Sandhya, S. (International Journal of Research in Medical Sciences, 2019)
Background: Most studies of lipid-lowering therapy for the prevention of coronary heart disease (CAD), focused on lowering low density lipoprotein cholesterol and non-HDL cholesterol. Other dyslipidemias, such as an elevated level of lipoprotein(a), also may promote atherosclerosis, establishment of relationship between lipoprotein(a) excess and risk for CAD, interventions directed toward altering these have only infrequently been evaluated in clinical trials. Objectives was to study the association of raised serum lipoprotein(a) in coronary heart disease. Methods: This study was conducted in 50 patients of CAD and 50 people as control group. All patients underwent a standard clinical examination and a blood draw for a lipid profile and lipoprotein(a) assay. Pearson chi-square test was used to assess the statistical significance. Results: Lipoprotein(a) value of more than 30 mg/dl is considered as elevated. In case group 19 patients (38%) were showed elevated lipoprotein(a) and in control group these were 9 patients (18%). p value is 0.026. It shows elevated lipoprotein(a) is statistically significant with the relative risk of 2.79. Conclusions: The association of elevated lipoprotein(a) with CAD was statistically significant. Higher lipoprotein(a) levels were observed in patient with family history of premature CAD.